Usefulness of a double immunofluorescence technique for detection of intestinal tTG-IgA deposits in diabetic and non-diabetic children with celiac disease - Raghav Lal; Ranjeet Bhardwaj; Ranjana Walker Minz; Kaushal Kishore Prasad; Sadhna Lal; Devi Dayal; Yashwant Kumar (Elsevier, 2023)
Background: Celiac disease (CD) is frequently associated with type I diabetes mellitus (T1D), where its diagnosis may be a challenging task. This study aims to test the usefulness of the double staining immunofluorescence (dsIF) technique for the detection of intestinal anti-tissue transglutaminase specific IgA antibody (tTG-IgA) deposits in CD and T1D children with coexisting CD. Methods: A total of 46 patients (30 cases of CD and 16 cases of T1D with CD) and 16 non-diabetic, non-celiac children were recruited. Endoscopic biopsies were taken and analyzed by light microscopy, quantitative histology (QH), and a dsIF technique. Results: Histologically, villous atrophy was most severe in CD, followed by T1D with CD, while all control biopsies except 1 were normal. QH showed a statistically significant difference in villous height (Vh), crypt depth (CrD), and Vh:CrD ratio between diabetic and non-diabetic patients with CD. dsIF technique could detect tTG-IgA deposits in 85.7% of cases of CD alone and 93.8% of biopsies from diabetic children. Surprisingly, deposits were more extensive in biopsies with minimal villous shortening. Also, all 5 biopsies from T1D patients with normal histology were dsIF positive. Conclusion: In-situ analysis of tTG-IgA immune deposits facilitates the detection of positive serology early-onset CD. Quantitative analysis may be used as an ancillary tool to increase the reliability of histological findings in these patients.